2015
DOI: 10.1016/j.psyneuen.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in HPA-axis and autonomic nervous system functioning in childhood anxiety disorders point to a chronic stress hypothesis

Abstract: Background: It is of debate whether or not childhood anxiety disorders (AD) can be captured by one taxonomic construct. This study examined whether perceived arousal (PA), autonomic nervous system (ANS) and hypothalamic-pituitary-adrenal (HPA) axis measures can distinguish children with different primary diagnoses of clinical anxiety disorders (AD) from each other, and from a general population reference group (GP). Methods: The study sample consisted of 152 AD children (comparing separation anxiety disorder, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 41 publications
6
83
1
Order By: Relevance
“…However, other studies in samples of undergraduate students have not found RSA differences between adults with high versus low trait anxiety (Wilhelm et al 2001), and the only study to employ the TSST in adults with anxiety disorders reported no differences between adults with anxiety disorders and those without (Klumbies et al 2014). Similar to the adult literature, studies of children with anxiety disorders have suggested lower PNS functioning at baseline (Dieleman et al 2015). Studies employing emotional regulation or trauma recall tasks in adolescents with anxiety disorders have shown no differences in RSA responsivity (Fisher and Newman 2013; Shenk et al 2014; Kirsch et al 2015) or have found differences in female, but not male adolescents (Hastings et al 2014).…”
Section: Discussionmentioning
confidence: 65%
“…However, other studies in samples of undergraduate students have not found RSA differences between adults with high versus low trait anxiety (Wilhelm et al 2001), and the only study to employ the TSST in adults with anxiety disorders reported no differences between adults with anxiety disorders and those without (Klumbies et al 2014). Similar to the adult literature, studies of children with anxiety disorders have suggested lower PNS functioning at baseline (Dieleman et al 2015). Studies employing emotional regulation or trauma recall tasks in adolescents with anxiety disorders have shown no differences in RSA responsivity (Fisher and Newman 2013; Shenk et al 2014; Kirsch et al 2015) or have found differences in female, but not male adolescents (Hastings et al 2014).…”
Section: Discussionmentioning
confidence: 65%
“…Subsequent work has shown that patients with schizophrenia, CHR and first-degree relatives appear to have abnormal dopamine release in response to metabolic or psychosocial stress induction (Brunelin et al, 2010;Lataster et al, 2013;Mizrahi et al, 2012). HPA abnormalities have, of course, also been identified in a range of mental health conditions (Dieleman et al, 2015;Gold, 2014;Het et al, 2014). This is not surprising given the multifaceted role of the HPA axis and the multiple sources of stress and adversity encountered in daily life.…”
Section: Implications Of a Tonic/phasic Model Of Hpa Axis Dysregulationmentioning
confidence: 99%
“…Additionally, emotional abuse has been noted to be more frequently and chronically experienced than other trauma types, which can exacerbate the degree of its effect (Burns et al, 2010;Sullivan et al, 2006). Unrelenting exposure to danger has been shown to be associated with anxiety but not depression in animal research (Chaby et al, 2015;Slattery et al, 2012), and similar psychophysiological alterations have been observed in children with severe anxiety disorders (Dieleman et al, 2015). Future research is needed to examine whether it is the chronicity of emotional abuse versus the nature of such abuse that contributes to ED, and whether this effect is specific to anxiety.…”
Section: Discussionmentioning
confidence: 99%